Interferência das plantas daninhas na cultura da mandioca em sistemas de plantio convencional e direto - Ramella, João Ricardo Pompermaier (2017)
Soil tillage systems as well as weed coexistence influence the development of the cassava plant and the dynamics of weeds, as well as productivity and the profitability of agricultural crops. The objective of this study was to determine the interference periods, PAI and PADRE, for the 1st and 2nd cycle of cassava 'IAC 90' cassava under conventional tillage (PC) and no-tillage systems (PD). Planting of the two experiments was carried out simultaneously and, before pruning (1st cycle = 10 months) and after pruning (2nd cycle = 10 months). In each experiment, a randomized complete block design with subdivided plots with four replications was used for the biometric parameters. For the PAI and PADRE values, the experimental design was a randomized block design with subdivided plots, with four replications. The plot represented the tillage of soil, the sub-plot the coexistence and the sub-plot the periods of coexistence. In the 1st and 2nd cycle, the treatments were constituted of 10 growing periods without and with weed coexistence (25, 50, 75, 100, 125, 150, 175, 200 and 225 days) after planting-DAP and post pruning -DAP/Po, besides a free plot and another with the presence of weeds. In both cycles, weed characteristics (plant density, relative importance and similarity index) and cassava plants (plant biometry, growth rates, leaf nutrient content, root and starch production) were evaluated. The PAI and PADRE were determined for each cycle. Data were submitted to analysis of variance and means to regression analysis. In the 1st cycle, the PAI for root productivity was 30 and 41 DAP for conventional tillage and no-tillage, respectively. For starch the PAI was 10 DAP for conventional tillage and 11 DAP for no tillage system. The PADRE for roots in the 1st cycle was between 17 and 42 DAP in the conventional tillage, and 23 and 56 DAP in the no-tillage system. For starch, the PADRE was between 6 and 15 DAP and 8 and 19 DAP for conventional tillage and no-tillage, respectively. In the 2nd cycle, the PAI for root was 14 DAP/Po in conventional tillage and 18 DAP/Po in no tillage system. For starch the PAI was 10 DAP/Po in both soil tillage systems. The PADRE for root was between 22 and 29 DAP/Po for conventional tillage and 29 and 38 DAP/Po for the no-tillage system. For starch, the PADRE was between 19 and 25 DAP/Po for both soil preparation systems. Soil tillage systems act on weed flows in the cultivated area and in the periods of interference in a different way for the 1st and 2nd cycle of 'IAC 90' cassava.